PENGARUH KONSENTRASI ISOPROPANOL TERHADAP KARAKTERISTIK KARBOKSIMETIL SELULOSA DARI BATANG PISANG - Ridwan Santoso (Inovasi Pembangunan : Jurnal Kelitbangan, 2020)
In this study consists of 5 stages, namely preparation of raw materials, cellulose isolation, alkalization, carboxymethylization, and purification. The raw material preparation stage is banana stem powder sieved at mesh 60. Furthermore, cellulose isolation of banana stems is carried out with 90% formic acid with a stirring speed of 300 rpm for 180 minutes at 100 0C. Alkalised using 15% NaOH and varying concentrations of 70%, 80%, 90% and 100% isopropanol solvents in a 100 rpm waterbath shaker for 60 minutes at 300C. The next step is carboxymethylation between alkali cellulose and trichloroacetic acid for 180 minutes at 550C in a 100 rpm waterbath shaker. At the purification glacial acetic acid and ethanol are used to remove unwanted by-products. The results characteristics with the highest degree of substitution value of 0.8 in the composition of 100% isopropanol, the highest purity of 99.7%, pH 4.8 and 5% moisture content.